Time-Line Based Aerial Analysis for Impact of Rampant Urbanization on Lakes of Bengaluru (India) - Gopinath, Rajesh; Cu, Akarsh; Me, Muralidhar (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Urbanization is introducing drastic transitions in the natural landscapes such as open areas, green spaces and water bodies of each and every city. The present study undertakes time line aerial analysis for 2 decades from 2000 to 2019 to comprehend the effect of urbanization upon the Lakes of Bengaluru. Once famed as the city of 1000 Lakes; its wetlands now pose serious concern in terms of quantity, quality, aesthetics, epidemics and as life support system for native aquatic species.
Keywords: lakes of Bengaluru; urbanization; satellite analysis; lakes; jeziora Bangalore; urbanizacja; analiza satelitarna; jeziora; krajobraz naturalny